2014
DOI: 10.1152/japplphysiol.01101.2013
|View full text |Cite
|
Sign up to set email alerts
|

Reduced skeletal muscle AMPK and mitochondrial markers do not promote age-induced insulin resistance

Abstract: GR. Reduced skeletal muscle AMPK and mitochondrial markers do not promote age-induced insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
(66 reference statements)
0
5
1
Order By: Relevance
“…Despite the well-documented role of AMPK activators improving insulin sensitivity, most studies have found that mice having reductions in skeletal muscle AMPK activity fed a control chow [25,34,40] or obesity-promoting HFD diet [40,41] have normal skeletal muscle insulin sensitivity compared to wildtype littermates; although it should be noted that some studies have detected modest reductions in muscle insulin sensitivity [17,42,43] . While previous studies have investigated the effects of an obesity-inducing HFD on a genetic background of lower muscle AMPK activity, it is possible that small amounts of residual AMPK activity may have been sufficient to maintain skeletal muscle insulin sensitivity in these previous reports [40,41] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the well-documented role of AMPK activators improving insulin sensitivity, most studies have found that mice having reductions in skeletal muscle AMPK activity fed a control chow [25,34,40] or obesity-promoting HFD diet [40,41] have normal skeletal muscle insulin sensitivity compared to wildtype littermates; although it should be noted that some studies have detected modest reductions in muscle insulin sensitivity [17,42,43] . While previous studies have investigated the effects of an obesity-inducing HFD on a genetic background of lower muscle AMPK activity, it is possible that small amounts of residual AMPK activity may have been sufficient to maintain skeletal muscle insulin sensitivity in these previous reports [40,41] .…”
Section: Discussionmentioning
confidence: 99%
“…Values were expressed to blood glucose and 2-[ 14 C] DG infusion in the blood. Additionally, lysates were used to measure cytochrome c oxidase (COX) activity, as described previously [34] . Blood was collected for serum biochemistry measurements post-hyperinsulinemic euglycemic clamp, including NEFA and insulin (Iso-insulin ELISA kit (Mercodia)).…”
Section: Methodsmentioning
confidence: 99%
“…AMPK is required for endurance exercise, because mice lacking AMPK subunits in skeletal muscle have a dramatically impaired ability to perform muscle contractions and forced treadmill running and also display reduced voluntary wheel running (O'Neill et al 2011;Lantier et al 2014). Despite these impairments, surprisingly, genetic removal of skeletal muscle AMPK does not promote the development of insulin resistance (O'Neill et al 2011;Bujak et al 2014;Lantier et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The most common AMPK heterotrimer in skeletal muscle is the a 2 , b 2 , g 1 (28). During aging, attenuation of skeletal muscle AMPK activity (29) is associated with alterations in the sarcolemmal environment, including reduced DAPC protein content (30)(31)(32)(33)(34). AMPK is a potent regulator of skeletal muscle phenotype primarily through phosphorylation-mediated changes in the expression and activity of downstream proteins capable of regulating phenotype maintenance and remodeling.…”
mentioning
confidence: 99%